Two Genomic Regions Contribute Disproportionately to Geographic Differentiation in Wild Barley. Issue 7 (1st July 2014) - Fang, Zhou; Gonzales, Ana M; Clegg, Michael T; Smith, Kevin P; Muehlbauer, Gary J; Steffenson, Brian J; Morrell, Peter L
Abstract: Genetic differentiation in natural populations is driven by geographic distance and by ecological or physical features within and between natural habitats that reduce migration. The primary population structure in wild barley differentiates populations east and west of the Zagros Mountains. Genetic differentiation between eastern and western populations is uneven across the genome and is greatest on linkage groups 2H and 5H. Genetic markers in these two regions demonstrate the largest difference in frequency between the primary populations and have the highest informativeness for assignment to each population. Previous cytological and genetic studies suggest there are chromosomal structural rearrangements (inversions or translocations) in these genomic regions. Environmental association analyses identified an association with both temperature and precipitation variables on 2H and with precipitation variables on 5H.